Landscape controls on spatiotemporal discharge variability in a boreal catchment. Issue 8 (25th August 2016) - Karlsen, R. H.; Grabs, T.; Bishop, K.; Buffam, I.; Laudon, H.; Seibert, J.
Abstract: Improving the understanding of how stream flow dynamics are influenced by landscape characteristics, such as soils, vegetation and terrain, is a central endeavor of catchment hydrology. Here we investigate how spatial variability in stream flow is related to landscape characteristics using specific discharge time series from 14 partly nested subcatchments in the Krycklan basin (0.12 – 68 km 2 ). Multivariate principal component analyses combined with univariate analyses showed that while variability in landscape characteristics and specific discharge were strongly related, the spatial patterns varied with season and wetness conditions. During spring snowmelt and at the annual scale, specific discharge was positively related to the sum of wetland and lake area. During summer, when flows are lowest, specific discharge was negatively related to catchment tree volume, but positively related to deeper sediment deposits and catchment area. The results indicate how more densely forested areas on till soils become relatively drier during summer months, while wet areas and deeper sediment soils maintain a higher summer base flow. Annual and seasonal differences in specific discharge can therefore be explained to a large extent by expected variability in evapotranspiration fluxes and snow accumulation. These analyses provide an organizing principle for how specific discharge varies spatially across the boreal landscape, and how this variation is manifested for different wetness conditions, seasons and time scales. Key Points: Novel analysis of both short and long term spatiotemporal specific discharge patterns in a boreal landscape Changing relationships of catchment characteristics and specific discharge depending on season and hydrological conditions Seasonal patterns largely explained by catchment characteristics related to snow accumulation and evapotranspiration